Quality, integrity and safety of Medicinal and Aromatic Plants (MAPs) and Wild Edibles from Indian Himalayan Arid Regions: OPINION PAPER - Agnihotri, Vasudha (Annals of Arid Zone, 2025)
The arid region of the Indian Himalayas is abundant in medicinal and aromatic plants (MAPs) as well as wild edible plants, which are vital to traditional healthcare systems, local livelihoods, and the growing nutraceutical and related markets. The challenging climate, delicate ecosystem, and limited farming practices make the wild populations susceptible to over harvesting, adulteration, and loss of authenticity. Deficiencies in the standardization of post-harvest processing and value addition practices undermine product integrity. This paper presents an opinion on the current quality assurance frameworks and the necessity for customized ones suited to the harsh conditions of the Himalayan arid regions.